2003
DOI: 10.1590/s0074-02762003000100002
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B virus infection among an afro-descendant community in Brazil

Abstract: Furnas dos Dionísios is an Afro-Brazilian black community whose descendants were mainly fugitive slaves that established themselves in the State of Mato Grosso do Sul (MS), 3%). While intrafamilial transmission was most likely responsible for HBV infection among children, other routes such as sexual contact might be considered for individuals with ages over 15 years.Key words: hepatitis B -Afro-descendants -seroprevalence -transmission -Brazil Hepatitis B virus (HBV) is believed to infect more than 350 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…Indeed, the Caribbean population mainly includes Africans who arrived during the slavery period between the 16th and 19th centuries. This supports the recent study by Westland et al [2003], which found that all patients with genotype E were African American, unlike several other studies performed in communities of Afro descent in the ''New World'' which failed to find the HBV/E genotype in these populations [Blitz et al, 1998;Teles et al, 1999;Motta-Castro et al, 2003].…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, the Caribbean population mainly includes Africans who arrived during the slavery period between the 16th and 19th centuries. This supports the recent study by Westland et al [2003], which found that all patients with genotype E were African American, unlike several other studies performed in communities of Afro descent in the ''New World'' which failed to find the HBV/E genotype in these populations [Blitz et al, 1998;Teles et al, 1999;Motta-Castro et al, 2003].…”
Section: Discussionsupporting
confidence: 87%
“…As observed elsewhere [21][22][23] , older age was associated with this infection. Age may be a proxy for lifetime exposure, indicating that, over time, there is a cumulative risk of HBV infection linked to sexual activity and percutaneous exposures.…”
Section: Ethicalsupporting
confidence: 81%
“…However, STD has been implicated and found to be a significant risk factor for HBV infection transmission in many previous studies [3] Ironically, more subjects in the rural Rift Valley region gave a history of having had an STD followed by Central region then Nairobi which by virtue of being a city would have been expected to have the highest prevalence of STD [17].…”
Section: Discussionmentioning
confidence: 99%